2005
DOI: 10.1086/502601
|View full text |Cite
|
Sign up to set email alerts
|

Varying Rates of Clostridium Difficile-Associated Diarrhea at Prevention Epicenter Hospitals

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. The University of Chicago Press and BACKGROUND:Clostridium difficile-associated diarrhea (CDAD) causes substantial healthcare-associated morbidity. Unlike other common healthc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
37
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 8 publications
0
37
1
Order By: Relevance
“…There may be a surveillance artifact: in different hospitals, the threshold for testing stool samples for C. difficile toxin may vary (especially in Quebec, where heightened public attention may have led to increased testing). Variation in toxin testing methods may also contribute, because these tests are not uniformly sensitive [19] Although it has been suggested that these discrepant findings may be the result of differing methodologies [20], this is not the case for our surveillance. Our study was conducted using a previously piloted methodology with a standardized case definition and patient questionnaire.…”
Section: Discussionmentioning
confidence: 90%
“…There may be a surveillance artifact: in different hospitals, the threshold for testing stool samples for C. difficile toxin may vary (especially in Quebec, where heightened public attention may have led to increased testing). Variation in toxin testing methods may also contribute, because these tests are not uniformly sensitive [19] Although it has been suggested that these discrepant findings may be the result of differing methodologies [20], this is not the case for our surveillance. Our study was conducted using a previously piloted methodology with a standardized case definition and patient questionnaire.…”
Section: Discussionmentioning
confidence: 90%
“…[12] A possible explanation for this lower burden of disease may be the generally younger SA hospital patient population. The median age in our study was 41 years.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors that could explain differences in the incidence of CDAD include the awareness of physicians of C. difficile-associated infections, as well as strategies and methods used in laboratories for C. difficile testing [30]. Although the definition used for CDAD, based on toxigenic culture, probably overestimated the number of cases by detecting carriers of toxigenic strains, the mean incidence (2.45 ⁄ 10 000 patient-days) remains much lower than that in the USA and Canada, where incidence rates range from 4 to >25 ⁄ 10 000 admissions [15,17,31,32]. To facilitate benchmarking and comparison of rates of CDAD among institutions, a more standardised case definition and strategy for C. difficile testing should be implemented, as suggested by a recent European working group on C. difficile [33].…”
Section: Discussionmentioning
confidence: 99%